Consumer and employer discrimination in professional sports markets - New evidence from Major League Baseball - Wolfgang Maennig; Steffen Q. Mueller (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2021)
We investigate the relationship between consumer discrimination, racial matching strategies, and employer discrimination in Major League Baseball (MLB) from 1985 to 2016. To this end, we assess the extent to which both fan attendance and team performance respond to changes in teams' and their local market areas' racial compositions. We innovate by using a significantly enhanced data basis with individual player data that we derive from combining web scraping and using facial recognition techniques to identify player race and using County-level Census data instead of Metropolitan Statistical Area data. We find that fans in both MLB Leagues developed a taste for racial diversity in the late 1980s; since the 2000s, discrimination starts to increase again. However, this discrimination is not fully rationalizing the performance gap across athletes of different race and ethnicity; employer discrimination is not primarily driven by fans' racial preferences.
Keywords: C5; J1; Z2; 330; Consumer preferences; Discrimination; Race; Ethnicity; Facial recognition; Ticket sales